Gender-wise comparison of oral health-related quality of life and its relationship with periodontal status among the Indian elderly - Charu Mohan Marya; Harpreet Singh Grover; Shourya Tandon; Pratibha Taneja; Anil Gupta; Vandana Marya (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study is to assess if there are any gender differences in oral health-related quality of life (OHRQoL) and periodontal status among the elderly population of Haryana. Materials and Methods: A cross-sectional study was conducted among 1200 geriatric population of Faridabad district of Haryana. Subjects were selected by a combination of systematic, cluster, and multistage sampling techniques. Primary, secondary, and tertiary sampling units were chosen as wards, areas, and households, respectively. Self-Administered Questionnaire: Geriatric oral health assessment index was used to assess the OHRQoL among males and females. Periodontal status was assessed using the World Health Organization oral health survey pro forma with some modifications. Results: Results were analyzed using the Statistical Package for the Social Sciences 21 software. Gender-wise association of periodontal status with OHRQoL revealed a significant association with mobile teeth (P < 0.05). No relation was seen between OHRQoL, gingival bleeding, periodontal pocket, and loss of attachment (P > 0.05). Conclusion: No significant differences were observed in periodontal status among males and females, but OHRQoL was found to be better among males than females. Indian policymakers can use the conclusion derived from this study for planning and implementing public oral health strategies for the geriatric population.